PENGARUH METODE PROBLEM SOLVING DAN KESIAPAN BELAJARSISWA TERHADAP HASIL BELAJAR PAK DI KELAS XI SMA NEGERI 2 BALIGE - Dewi Sartika Sitepu (Universitas Negeri Medan, 2019)
The purpose of this study is to take learning material on Christian attitudes in the development of science. The research subject was 28 students in Class XI of SMA 2 Balige. The results of the study concluded that using the jigsaw method can improve student learning motivation. Increasing student learning motivation in the pre-cycle is 50%,% (14 students) to 71.4% (20 students) in Cycle II, to 85.71% (25 students). As per the data above, it can be interpreted that the motivation to learn has been dominated by some 96.42% of students. Thus, looking at learning outcomes at the initial observation, there appears to be a significant percentage increase in completeness of student learning outcomes from 50% (14 students) to 71.4% (20 students) in Cycle II, to 85.71% (25 people students), to 96.42% (27 students). Keywords: Learning Readiness, Problem Solving Method, learning outcomes